THE ROLE OF MEDICAL STAFF IN THE CARE OF PATIENTS WITH NON-COMMUNICABLE DISEASES (Multidisciplinary Journal of Science and Technology, 2025)
This scientific article provides an in-depth analysis of the role and importance of medical staff in the care of patients with non-communicable diseases (non-communicable diseases). The article considers global and Uzbek statistical data, the causes of diseases, the tasks of medical staff (including nurses and paramedics) in prevention, monitoring and education, as well as difficulties and solutions in their activities. The study emphasizes the central role of paramedics in the prevention and management of noncommunicable diseases, based on scientific evidence and Uzbek legislation, aimed at ensuring quality medical care and improving the quality of life of the population.